Personalized 3D printed bone scaffolds: A review. (15th January 2023) - Mirkhalaf, Mohammad; Men, Yinghui; Wang, Rui; No, Young; Zreiqat, Hala
Abstract: 3D printed bone scaffolds have the potential to replace autografts and allografts because of advantages such as unlimited supply and the ability to tailor the scaffolds' biochemical, biological and biophysical properties. Significant progress has been made over the past decade in additive manufacturing techniques to 3D print bone grafts, but challenges remain in the lack of manufacturing techniques that can recapitulate both mechanical and biological functions of native bones. The purpose of this review is to outline the recent progress and challenges of engineering an ideal synthetic bone scaffold and to provide suggestions for overcoming these challenges through bioinspiration, high-resolution 3D printing, and advanced modeling techniques. The article provides a short overview of the progress in developing the 3D printed scaffolds for the repair and regeneration of critical size bone defects. Statement of significance: Treatment of critical size bone defects is still a tremendous clinical challenge. To address this challenge, diverse sets of advanced manufacturing approaches and materials have been developed for bone tissue scaffolds. 3D printing has sparked much interest because it provides a close control over the scaffold's internal architecture and in turn its mechanical and biological properties. This article provides a critical overview of the relationships between material compositions, printing techniques, and properties of the scaffolds and discusses the current technical challenges facing their successful translation to the clinic. Bioinspiration, high-resolution printing, and advanced modeling techniques are discussed as future directions to address the current challenges. Graphical abstract: Image, graphical abstract .